Mere Christianity : comprising the case for Christianity, Christian behavior and beyond personality - Lewis, C. S. (Clive Staples), 1898-1963. (New York : Simon and Schuster, 1984)
Rev. ed. first published in 1952.
Keywords: Theology, Doctrinal -- Popular works; Apologetics; Christian ethics -- Anglican authors; Lewis, C.S. (Clive Staples), 1898-1963 -- Religion